Hubungan Pengetahuan Dan Self Control Dengan Perilaku Merokok Pada Remaja Di SMP Negeri Selangit Musi Rawas Utara Tahun 2025 - Eis Sian Nora; Yance Hidayat; Emi Pebriani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Indonesia is one of the largest cigarette consuming countries in the world. The Indonesian Health Survey (2023) found that the prevalence of smoking among the population aged ≥10 years was 22.46% daily smokers and 4.56% occasional smokers. Based on the age of adolescents aged 10-14 years, daily smokers were 0.5% and occasional smokers were 0.7%. Adolescents aged 15-18 years old smoked daily by 11.1% and occasional smokers by 5.6%. The purpose of this study was to determine the relationship between knowledge and self-control with smoking behavior in adolescents at Selangit State Junior High School, North Musi Rawas in 2025. The research method used was descriptive research with a cross-sectional approach. The sampling technique used Proportionate Stratified Random Sampling with a sample size of 72 adolescents at Selangit State Junior High School, North Musi Rawas in 2025. The results of the univariate test analysis showed that most of the respondents (52.8%) had sufficient knowledge, most of the respondents (52.8%) had moderate self-control, and almost half of the respondents (48.6%) had smoking behavior. The results of the bivariate analysis showed a relationship between knowledge (p-value 0.000) and self-control (p-value 0.000) with smoking behavior in adolescents. There is a relationship between knowledge and self-control with smoking behavior in adolescents at Selangit State Junior High School, North Musi Rawas in 2025. The researcher recommends that respondents use their knowledge to make healthy lifestyle choices, avoid smoking, and be a positive role model for their peers.